Eat for energy : how to beat fatigue, supercharge your mitochondria, and unlock all-day energy - Whitten, Ari; Leaf, Alex (Hay House, Inc., 2022)
"Now is the time for you to have the energy to live the life of your choosing. Chronic fatigue, burnout, brain fog-no matter what we call it, our constant feeling of being drained affects all that we hold dear. There are very real culprits of our fatigue, and they don't lie in our preconceived notions of caffeine intake or adrenal fatigue, nor does the replenishment of our energy lie in overhauling our lifestyle in time-consuming and unrealistic ways. Instead, the core underlying cause lies in our cells, specifically our mitochondrial deficiency, and the solution can be found in simple, straightforward, nutritional strategies that address our body's biology. Ari Whitten, functional health practitioner and creator of The Energy Blueprint program, takes you on a deep dive of our cellular energy centers, exploring the biggest stressors that affect our mitochondria and the holistic workings of our body systems"--